Value creation in private equity: Evidence from Finnish transactions - Haikkola, Jan-Patrick (My University, 2018)
This thesis aim is to examine the value creation and different value creation levers on a deal-level for private equity leverage buyout transactions. Furthermore, the focus is on Finnish private equity transactions and the significance and relationship of identified value creation levers on the value creation. The thesis data is a unique sample of 108 sanitized Finnish private equity transactions with entry and exit level financial data for different private equity backed companies. The first observed private equity investment is in 1991 and the last observed private equity exit is in 2016, and thus the time-period for the sample is 1991 to 2016. The entry and exit level transaction data allows this thesis to investigate the change in enterprise value and different variables that affect it. The variables that are used to examine the change in enterprise value are identified based on the previous academic research on the topic with EBITDA-margin, revenue growth, EBITDA-multiple expansion and leverage effect chosen for the variables. The methodology is also based on previous studies on value creation with OLS-regression created to test the hypotheses. The thesis main findings are mainly consistent with the previous academic literature on value creation in private equity. EBITDA-margin, revenue growth and EBITDA-multiple is found to have a statistically significant positive relationship with change in enterprise value, while leverage effect is not statistically significant.
Keywords: Alternative investments; private equity; leveraged buyouts; value creation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|